Factors that differentiate distressed and non-distressed marriages in army soldiers - Anderson, Jared R.; Johnson, Matthew D.; Goff, Briana S. Nelson; Cline, Laura E.; Lyon, Sarah E. (My University, 2013)
Data from U.S. Army soldiers (N = 697) were analyzed to determine the factors that differentiate distressed from non-distressed relationships. Results show that most soldiers had relationship satisfaction scores that categorized them as non-distressed. In addition, soldiers in dual-military marriages had relationship satisfaction scores similar to those of soldiers in military-civilian marriages. Finally, several variables including rank, relocation status, relationship length, and relationship status differentiated distressed from non-distressed relationships. Implications for intervention programming and future research directions are discussed.
Keywords: Dual-military couples; Military marriages; Relationship distress